Suprapatellar versus infrapatellar approach for intramedullary nailing in tibial shaft fractures - Lone, Aadil Hussain; Rather, Aabid Ahmad; Bhat, Aamir Nazir; Maajid, Saheel; Khan, Kafeel (International Journal of Research in Medical Sciences, 2023)
Background: Tibial shaft fractures accounts about 2% of all adult fractures and it is a common traumatic injury caused by high-energy trauma. The intra-medullary nail fixation either by Suprapatellar approach or Infrapatellar approach has been reported to be a successful surgical procedure for the treatment of proximal tibia fractures. Aim was to compare the clinical and functional outcomes of tibial shaft fractures treated with IMN using the suprapatellar and infrapatellar methods. Methods: The present prospective comparative study was conducted to compare the clinical and functional outcomes of tibial shaft fractures managed by Suprapatellar or Infrapatellar intramedullary nailing technique. This study was conducted in the Post Graduate Department of Orthopedics in SKIMS, MCH Bemina, Srinagar for a period of 02 years from May, 2020 to May, 2022. A total of 40 patients with tibial shaft fracture were included in the study. The statistical analysis was done using SPSS (Statistical Package for the Social Sciences, SPSS Inc., v.16). Results: It was observed that the majority of the participants (37.5%) were in 31-40 year’s age group, there were male predominance with the male to female ratio 2.33:1. In SP technique excellent results were observed in 80% of the study subjects whereas in IP technique, 70% patients had excellent results. Conclusions: It is concluded that SP technique shows better results as compared to IP technique in the management of tibial shaft fracture.